Flattening of the Phillips Curve : Implications for Monetary Policy - Iakova, Dora. (Washington, D.C. : International Monetary Fund, 2007)
Over the past decade, inflation has become less responsive to domestic demand pressures in many industrial countries. This development has been attributed, in part, to globalization forces. A small macroeconomic model, estimated on UK data using Bayesian estimation, is used to analyze the monetary policy implications of this structural change. The focus is on the implications of a globalization-related flattening of the Phillips curve for the trade-off between inflation and output gap variability and for the efficient monetary policy response rule.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Efficient Monetary Policy Rules; Globalization; Inflation Expectation; Phillips Curve; WP; United Kingdom